I think its the first and fourth tv
Answer:
59
Step-by-step explanation:
1. -35
2. +9
3. -23
4. +3
5. +5
6. -7
7. +125
8. -18
Add them all up in a calculator and you get 59
Answer:
x = 6
Step-by-step explanation:
Given
6x² - 2x + 36 = 5x² + 10x ( subtract 5x² + 10x from both sides )
x² - 12x + 36 = 0 ← in standard form
This is a perfect square of the form
(x - a)² = x² - 2ax + a²
36 = 6² ⇒ a = 6 and 2ax = (2 × 6)x = 12x, hence
(x - 6)² = 0
x - 6 = 0 ⇒ x = 6
<span>8√5 + 2√45
= </span><span>8√5 + 6√5
= 14</span>√5
hope it helps
i will solve it first i need full form